Microbial diversification is maintained in an experimentally evolved synthetic community - Zahraa Al-Tameemi; Alejandra Rodríguez-Verdugo (mSystems)
ABSTRACT Microbial communities are incredibly diverse. Yet, the eco-evolutionary processes originating and maintaining this diversity remain understudied. Here, we investigate the patterns of diversification for Pseudomonas putida evolving in isolation and with Acinetobacter johnsonii leaking resources used by P. putida. We experimentally evolved four experimental replicates in monoculture and co-culture for 200 generations. We observed that P. putida diversified into two distinct morphotypes that differed from their ancestor by single-point mutations. One of the most prominent mutations hit the fleQ gene encoding the master regulator of flagella and biofilm formation. We experimentally confirmed that fleQ mutants were unable to swim and formed less biofilm than their ancestor, but they also produced higher yields. Interestingly, the fleQ genotype and other mutations swept to fixation in monocultures but not in co-cultures. In co-cultures, the two lineages stably coexisted for approximately 150 generations. We hypothesized that A. johnsonii modulates the coexistence of the two lineages through frequency-dependent selection. However, invasion experiments with two genotypes in monoculture and co-culture did not support this hypothesis. Finally, we conducted an evolutionary “replay” experiment to assess whether the presence or absence of A. johnsonii influenced the coexistence of morphotypes at the population level. Interestingly, A. johnsonii had a stabilizing effect on the co-culture. Overall, our study suggests that interspecies interactions play an important role in shaping patterns of diversification in microbial communities.IMPORTANCEIn nature, bacteria live in microbial communities and interact with other species, for example, through the exchange of resources leaked into the external environment (i.e., cross-feeding interactions). The role that these cross-feeding interactions play in shaping patterns of diversification remains understudied. Using a simple bacterial system in which one species cross-feeds resources to a second species (commensal species), we showed that the commensal species diversified into two subpopulations that persisted only when the cross-feeder partner was present. We further observed loss-of-function mutations in flagellar genes that were fixed in monocultures but not in co-cultures. Our findings suggest that cross-feeding species influence patterns of diversification of other species. Given that nutrient leakage is pervasive in microbial communities, the findings from this study have the potential to extend beyond our specific bacterial system. Importantly, our study has contributed to answering the larger question of whether species evolved differently in isolation versus when interacting with other species.